2007
DOI: 10.1074/jbc.m700398200
|View full text |Cite
|
Sign up to set email alerts
|

The Helicobacter pylori Amidotransferase GatCAB Is Equally Efficient in Glutamine-dependent Transamidation of Asp-tRNAAsn and Glu-tRNAGln

Abstract: The amide aminoacyl-tRNAs, Gln-tRNA Gln and Asn-tRNA Asn , are formed in many bacteria by a pretranslational tRNAdependent amidation of the mischarged tRNA species, Glu-tRNA Gln or Asp-tRNA Asn . This conversion is catalyzed by a heterotrimeric amidotransferase GatCAB in the presence of ATP and an amide donor (Gln or Asn). Helicobacter pylori has a single GatCAB enzyme required in vivo for both Gln-tRNA Gln and Asn-tRNA Asn synthesis. In vitro characterization reveals that the enzyme transamidates Asp-tRNA Asn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
154
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(175 citation statements)
references
References 47 publications
9
154
1
Order By: Relevance
“…In this study, the gene corresponding to M. catarrhalis tRNA Asn was artificially formed by hybridizing two phosphorylated oligonucleotides, 59-AATTCGGGGTATCGCCAAGTTGGTAAGGCATCAGGTTTTGAT-CCTGACATTCGTTGGTTCGAGTCCAGCTACCTCTGCCACTGC-A-39 and 59-GTGGCAGAGGTAGCTGGACTCGAACCAACGAAT-GTCAGGATCAAAACCTGATGCCTTACCAACTTGGCGATACCC-CG-39, and the gene was inserted into the sites EcoRI/PstI of pGFIB to create the pGFIB/MctRNA Asn clone. M. catarrhalis tRNA Asn was prepared according to Sheppard et al (2007). Analysis by electrophoresis on a 12 % polyacrylamide gel containing 8 M urea revealed that more than 99 % of the material was tRNA; its acceptor activity for Asn varied from 11 to 25 %.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the gene corresponding to M. catarrhalis tRNA Asn was artificially formed by hybridizing two phosphorylated oligonucleotides, 59-AATTCGGGGTATCGCCAAGTTGGTAAGGCATCAGGTTTTGAT-CCTGACATTCGTTGGTTCGAGTCCAGCTACCTCTGCCACTGC-A-39 and 59-GTGGCAGAGGTAGCTGGACTCGAACCAACGAAT-GTCAGGATCAAAACCTGATGCCTTACCAACTTGGCGATACCC-CG-39, and the gene was inserted into the sites EcoRI/PstI of pGFIB to create the pGFIB/MctRNA Asn clone. M. catarrhalis tRNA Asn was prepared according to Sheppard et al (2007). Analysis by electrophoresis on a 12 % polyacrylamide gel containing 8 M urea revealed that more than 99 % of the material was tRNA; its acceptor activity for Asn varied from 11 to 25 %.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, most bacteria and all archaea lack GlnRS and use an ND-GluRS and GatCAB or GatDE as a Glu-tRNA AdT (Glu-AdT) to form Gln-tRNA Gln (Curnow et al, 1997;Horiuchi et al, 2001;Sheppard et al, 2007Sheppard et al, , 2008; reviewed by Huot et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 GatCAB is present in most bacteria and archaea. 2,3,6 In vitro, the bacterial GatCAB can transamidate both Glu-tRNA Gln and Asp-tRNA Asn . 2, 12-15 Its role in vivo is determined by which mischarged tRNA species (Glu-tRNA Gln and/or Asp-tRNA Asn ) is present.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] 2) The AdTs have a glutaminase subunit (GatA and GatD, respectively) to liberate ammonia from an amide donor such as Gln or Asn. 2,20,23,24 GatD belongs to the type I L-asparaginase (AnsA) family 3, 20, 23 while GatA is an amidase. 2, 10, 21, 24 GatC, a small protein of approximately 100 amino acids, is required by GatA for proper folding 10 and binding to GatB.…”
Section: Introductionmentioning
confidence: 99%